PENERIMAAN PAJAK RESTORAN DAN PAJAK DAERAH - Syarif, Mahdan (Jurnal Ilmu Administrasi Negara, 2016)
Tax Revenues Restaurant and Local Tax. The research objective was to determine the effect of tax revenue to the local tax restaurant in the Department of Revenue, Finance and Asset Management District Siak. The informants were officials at the Department of Revenue, Finance and Asset Management. Secondary data collection techniques using time series analysis unit budget financial results Siak Siak district budget. Data were analyzed using simple regression test. The results showed that the restaurant tax receipts have an influence on increasing local tax revenues, although not show optimal results.